Instructional Strategy to Train Professors from the Civil Engineering Program in the Use of Information and Communications Technologies (ICTS) at the Villavicencio Campus of the Universidad Cooperativa de Colombia - Vargas Guativa, Javier Andrés; Arango Carrillo, Jeison; Isaza Domínguez, Lauren Genith (Ingeniería Solidaria, 2014)
The article summarizes the results of research carried out in 2012, entitled “Instructional Strategy to Train Professors from the Civil Engineering Program in the Use of Information and Communications Technologies (ict) as part of the Civil Engineering Program at the Villavicencio Campus of the Universidad Cooperativa de Colombia” (“Estrategia instruccional para la formación de docentes en el uso de las tecnologías de la información y las comunicaciones (tic) adscritos al programa de Ingeniería Civil de la Universidad Cooperativa de Colombia, sede Villavicencio”). The instructional strategy is a form of planning, organization and execution of situations, moments and contents aimed at strengthening and supporting the teaching–learning process. The research began with an initial diagnosis that showed that a large percentage (90%) of professors from the Civil Engineering Program at the Villavicencio campus of the Universidad Cooperativa de Colombia do not regularly use icts in their teaching methods; they also demonstrate minimal mastery of platforms, environments and virtual learning objects and synchronous and asynchronous communication tools. To solve this problem, the authors designed a strategy with virtual tools that are useful in the teaching-learning process for Civil Engineering. The article explains how the instructional strategy was designed for training Civil Engineering professors.